Seeded optical parametric generation in CdSiP2 pumped by a Raman fiber amplifier at 124 µm - Murray,RT; Chandran,AM; Battle,RA; Runcorn,TH; Schunemann,PG; Zawilski,KT; Guha,S; Taylor,JR (Optics Letters, 2021)
We report a seeded optical parametric generator (OPG) producing tunable radiation from 4.2–4.6 µm. The seeded OPG employs a 13 mm long CdSiP2 (CSP) crystal cut for non-critical phase-matching, pumped by a nanosecond-pulsed, MHz repetition rate Raman fiber amplifier system at 1.24 µm. A filtered, continuous-wave fiber supercontinuum source at 1.72 µm is used as the seed. The source generates up to 0.25 W of mid-infrared (MIR) idler power with a total pump conversion of 42% (combined signal and idler).